Neoadjuvant and Adjuvant Surgical Interventions in Oncology: Optimizing Treatment Pathways - Eskandar, Kirolos (Indonesian Journal of Cancer Chemoprevention, 2024)
The advancement of cancer treatment has seen significant progress through the integration of neoadjuvant and adjuvant therapies, particularly within the realm of surgical oncology. This literature review follows a systematic approach using PRISMA guidelines, analyzing studies from databases such as PubMed, Google Scholar, Scopus, and Web of Science. The review examines the historical progression, current practices, and future directions of multimodal approaches, focusing on the synergistic benefits of surgery, drug development, targeted therapies, and technological innovations. Neoadjuvant interventions, designed to shrink tumors preoperatively, enhance surgical outcomes by improving resectability, while adjuvant therapies, administered postoperatively, aim to eliminate residual disease and reduce recurrence risk. Findings from clinical trials and case studies highlight improved survival rates, increased tumor resectability, and enhanced patient outcomes through the combination of these therapies. Additionally, the review emphasizes the crucial role of personalized medicine, molecular profiling, and emerging surgical technologies in refining treatment pathways. As the landscape of cancer care evolves, optimizing treatment sequencing and tailoring therapies to individual tumor profiles will be essential for maximizing therapeutic efficacy and improving patient prognosis.Keywords: Neoadjuvant Therapy, Adjuvant Surgical Intervention, Surgical Oncology, Multimodal Cancer Treatment, Targeted Cancer Therapy.